2020
DOI: 10.3390/molecules25071704
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamoyl Amino Acids Conjugates: A Chiral Pool to Distinguish Commercially Exploited Coffea spp.

Abstract: The synthesis of five hydroxycinnamoyl amides (HCAs) was accomplished and their identification and quantification in the green coffee bean samples of Coffea arabica, Coffea canephora, and Coffea liberica was performed. The HCAs p-coumaroyl-N-tyrosine 1b, caffeoyl-N-phenylalanine 2b, caffeoyl-N-tyrosine 3b, and p-coumaroyl-N-tryptophan 4b were characteristic of the C. canephora species while caffeoyl-N-tryptophan 5b was present in both C. canephora and C. arabica, but with higher content in C. canephora. The HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…The MN ( Figure 1 C) showed most of the identified hydroxycinnamoyl amides, as identified in Table 2 , indicating their structural similarities. The results were in agreement with the previous literature distinguishing C. robusta products from other Coffea species-containing analogues [ 46 ].…”
Section: Resultssupporting
confidence: 93%
“…The MN ( Figure 1 C) showed most of the identified hydroxycinnamoyl amides, as identified in Table 2 , indicating their structural similarities. The results were in agreement with the previous literature distinguishing C. robusta products from other Coffea species-containing analogues [ 46 ].…”
Section: Resultssupporting
confidence: 93%
“…Overall, the amino acid conjugates of hydroxycinnamic acids (e.g., Na- p -hydroxy-coumaroyl-tryptophan) have been previously reported as potential marker compounds to discriminate among coffee cultivars [ 29 ]. In this regard, [ 30 ] showed that p -coumaroyl-N-tryptophan was a characteristic marker compound of the C. canephora species, thus confirming our findings. Also, the compound coffeasterene belongs to the class of organic compounds known as stigmastanes and derivatives.…”
Section: Resultssupporting
confidence: 90%
“…Chlorogenic acids were annotated in various green coffee specimens based on LC-MS 4 patterns of fragmentation, including derivatives of dimethoxycinnamoylquinic acids, caffeoyl-dimethoxycinnamoylquinic acids, and diferuloylquinic acids [ 46 ], in addition to hydroxycinnamoyl amides [ 47 ]. Additionally, roasting changes the coffee chemical profile and increases its complexity, due to the formation of quinides, chlorogenic derivatives, and shikimates.…”
Section: Metabolomics Applications In Coffee Roastingmentioning
confidence: 99%
“…LC/MS has been applied for studying the non-volatile metabolites associated with coffee brewing, including polyphenolics, alkaloids, and diterpenes. Compared to roasting effects, the effects of brewing on phytochemical composition, particularly chlorogenic acid and hydroxycinnamoyl amide derivatives, has not been extensively reported [ 46 , 47 ]. LC/MS showed potential in detecting health-related metabolites, either undesirable as acrylamide and furans, or desirable as the antioxidant phenolics, providing a good readout of coffee safety and efficacy of coffee prepared by cold methods [ 64 , 82 ].…”
Section: Metabolomics Applications In Coffee Brewingmentioning
confidence: 99%